P17 IBD admission avoidance during COVID-19. (19th June 2022) - Cousin, James; Boal, Allan; Squires, Seth; Naismith, Graham
Abstract : Introduction: The COVID-19 global pandemic provided significant challenges in service provision for inflammatory bowel disease (IBD) centres across the UK. Some of the key factors influencing this were the redeployment of clinical staff, reduction of face-to-face consultations and isolation guidance for both staff and patients. We looked at how the IBD team in the Clyde sector of NHS Greater Glasgow & Clyde reacted to these challenges. Specifically, the way they avoided patient admissions to acute hospital settings through the use of continuing telephone consultations from IBD specialist nurses and early introduction of definitive treatment such as biologic therapy. There was very limited evidence at that time of how contracting COVID-19 impacted immunosuppressed IBD patients, admission avoidance was therefore a priority. Methods: The timeframe period examined from 23/03/21 to 28/06/21 was defined as the "first wave" of COVID-19 at this site – coinciding with the redeployment of clinicians away from their regular IBD commitments. All gastroenterology consultant clinics were cancelled during this period to offer support to general medicine. We identified a total of 87 patients for whom the absence of specialist IBD advice would have led to ED attendance or GP consultation. Results: We identified 87 patients in this period who avoided admission to acute medical wards through IBD helpline screening rather than otherwise attending ED or contacting their GP. Instead, they were treated as arranged appointments in one-stop medical day units. Patients were either treated with new initiation of biologic therapy (43%); high-dose steroids (34%); intravenous iron infusions (4.5%); a combination of steroids plus biologic therapy (9%) or the use of foam enemas (2%). A significant number of these patients were started on biologics as initial first line therapy (n=37) in comparison to the usual titrate up protocol in an attempt to increase remission rates more rapidly during the COVID-19 pandemic. of these biologics, adalimumab was by far the most commonly used (67.5%), followed by ustekinumab (19%) and infliximab (8%). There were a minority of patients (4.5%) identified who did not require any intervention, but likely would have required admission without early specialist advice. Conclusions: IBD specialist teams are required to keep core members to ensure appropriate screening of patients plus enabling early access to most appropriate treatments. These data suggest that an IBD CNS team can provide a much needed input helping prevent front door pressures during a pandemic. Additionally, early screening from IBD teams can reduce pressures on primary care where services were similarly under strain. Overall, significant care must be taken to ensure a functioning IBD team is available to screen patients early to ensure patient safety and optimal disease management.